(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-1-129-137 The article analyzes the originality of the genre of Magomed-Rasul’s book “The Clairvoyant Foolˮ. Dagestan literature of the 20th century is literature of “eternal themesˮ. The writers sought to answer the difficult questions of existence: about the meaning of life, about the Homeland, about the purpose of man, about the laws of the universe. The Dargin writer Magomed-Rasul Rasulov, a novelist, a literary critic and a playwright, became famous in the 60s of the 20th century, whose works became a significant phenomenon in the literary life of Dagestan. The work of the people’s writer of Dagestan Magomed-Rasul Rasulov has become widely known in the republic and in the country as a whole. Almost all the works of the Dargin author have been translated into Russian, and foreign readers are familiar with some of them. Magomed-Rasul Rasulov is equally successful as an author of essays, short stories, novellas and novels. As a person with an active life and social position, Magomed-Rasul Rasulov could not stand aside from the important problems of his time. His works have been repeatedly published on the pages of the center. The relevance of this work is dictated by the fact that the antinarrative “Clairvoyant Foolˮ for the first time becomes the object of special study. The purpose of the research is to consider the problems and artistic features of the work and is implemented by solving the following interrelated tasks: consideration of plot and compositional features, definition of problems and identification of artistic features. The article uses sociocultural, analytical research methods. Key words: Dagestan literature, Dargin prose, genre, antinarrative, Magomed-Rasul Rasulov, artistic features